2020
DOI: 10.5530/pc.2020.2.13
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Pharmacological Potential of Galantamine

Abstract: Introduction: Galantamine a traditional herb has also been explored for a number of pharmacological effects. Today, galantamine has been observed for its nootropic effect. Methodology: The objective of this review is to study the evidence of effectiveness and pharmacological effects of galantamine. The preclinical and randomized controlled clinical trials pertaining to studies of galantamine are included. Chemical properties of galantamine and its structure activity relationship pertaining to various biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The absence of statistically significant differences in plasma BuChE activity between the GAL/INF group and the other groups studied reinforces the mechanism of action of galantamine on AChE, as previously reported. According to Upadhyay et al, 43 galantamine presents a selectivity that is 10 times more than AChE in relation to BuChE.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of statistically significant differences in plasma BuChE activity between the GAL/INF group and the other groups studied reinforces the mechanism of action of galantamine on AChE, as previously reported. According to Upadhyay et al, 43 galantamine presents a selectivity that is 10 times more than AChE in relation to BuChE.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on displacement of [3H] QNB and [3H] nicotine binding have revealed effects of HupA on cholinergic receptors compared to other AChEIs including galantamine and tacrine. 27 HupA lacks an effect on muscarinic receptors, whereas huprine X, a hybrid between tacrine and HupA, exhibited micro molar activity at M(1) and M(2) receptors, mostly agonistic. This additional muscarinic activity of huprineX is significant and offers therapeutic advantages in dementia therapy.…”
Section: Cholinergic Receptorsmentioning
confidence: 99%
“…It's been studied for Alzheimer's disease and other central nervous system disorders in various ways. The bioactive molecule galantamine was unintentionally found in the early 1950s, and plant extracts were first employed to treat nerve pain and poliomyelitis, according to the pharmacological history of galantamine 1 . In the early 1950s, galantamine was developed as a clinically useful medication.…”
Section: Introductionmentioning
confidence: 99%
“…According to sources, a Russian pharmacologist discovered that local peasants living at the foot of the Ural Mountain utilised wild Caucasian snowdrop to cure poliomyelitis in children 2 . Galantamine's AChE inhibitory capabilities and antagonising effects on curare activity were discovered in a research published in 1951 1 . Galantamine was initially discovered in 1952 from the perennial herbaceous plant Galanthus woronowii of the Amaryllidaceae family 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation